Pengaruh Metode Demonstrasi Menggunakan Laboratorium Virtual dan Riil Terhadap Keterampilan Proses Sains Siswa - Hizbi, Tsamarul (Kappa Journal, 2019)
This study aims to determine the effect of demonstration methods using virtual and real laboratories on science process skills of class VIII students of SMPN 2 Sikur 2018/2019 academic year. This type of research is experimental research, with post test only control group design. The population in this study were all eighth grade students who numbered 4 classes. The sample was determined by cluster sampling technique, and class VIII-B was obtained as the experimental class and VIII-D as the control class. The data collection technique used is the test technique. Test techniques are used to measure students' science process skills in science subjects. The prerequisite test used is the data normality test using Kolmogorov smirnov and the homogeneity test using Leaven Test with a significance of 5% in SPSS Version 20. While to test the hypothesis in the study using the Independent T-Test Sample Test on SPSS Version 20. The conclusions of this study are average the average score of the experimental class post test is higher than the average grade of control class VIII students at Sikur 2 Public High School 2018/2019.